METODE REPLIKASI KEWIRAUSAHAAN SOSIAL UNTUK PENINGKATAN MOTIVASI WIRAUSAHA BERBASIS KOMODITAS LOKAL DI KECAMATAN BANYURESMI, KABUPAPEN GARUT - Anas Bunyamin; Dwi Purnomo; Salamun Taofik (JURNAL AGROTEKNOLOGI, 2016)
Motivation in establishing entrepreneurship are often decreases over time as many obstacles were undertaken. It is going deeper whenit is happened toa local commodity-based business. Corn is a local commodity that is well developed in Banyuresmi, Garut, West Java. Corn rice development as one of the alternative of non-rice food does not necessarily succeed because people are less equipped with business skills. The main obstacle faced by the society is the lack of continuity of assistance. An intensive assistance can continuously improve their motivation in running the business. To overcome this condition, a replication method was developed with the objective of keeping the well developed entrepreneurial spirit be induced to the society of Banyuresmi. Replication method by presenting the society of corn rice businesses in other business units thatis already well under way was able to increase the motivation of the society. The proximity of the process being undertaken by the society with FruitsUp business has increased public confidence to proceed in developing a local commodity-based business. Keywords: entrepreneurhip replication, corn rice, business spirit